Research on partition evaluation method of fatigue strength of cast aluminum cylinder head - LÜ ZhenGuo; ZHOU HaiTao; ZHOU ZhiGe; JING GuoXi; LI ShuBo; LIU YiPeng; HE XiaoDong; LI Peng (Jixie qiangdu)
In order to consider the influence of mechanical properties of different at p positions of cylinder head on fatigue assessment, a fatigue assessment method considering the dispersion of mechanical properties of cylinder head was proposed. Firstly, samples were taken from the top plate, bottom plate, intake and exhaust port walls and vertical walls of the cylinder head body, and tensile tests were carried out to analyze the dispersion of mechanical properties of each part. Then, the microstructure characteristics of each area of the cylinder head were measured, and a prediction model of tensile properties based on microscopic defects was established. A fatigue strength prediction model was established by using the relation between tensile properties and fatigue strength. Finally, based on the multi-axial high-cycle fatigue theory, combined with the coupled thermo-mechanical stress and material boundary, a zonal evaluation method for the fatigue strength of the cylinder head was proposed. The results show that the prediction error of the established mechanical performance model is about 2%, which can accurately predict the mechanical performance of each area of the cylinder head. Compared with the traditional fatigue assessment method, the proposed method combined the influence of two factors of working load and material dispersion, and the estimated dangerous position was consistent with the test cracking position, so it can more accurately characterize the fatigue performance of the cylinder head.